Effects of Gender-Based Violence Towards Young Females: The Case of Vhufuli Village in Thohoyandou, Limpopo Province-South Africa - Thobejane, Tsoaledi (Journal of Reviews on Global Economics, 2019)
Gender based violence towards young women is a pandemic experienced mostly by women of all classes and age in different settings, spheres of life and environment. It affects the victim both socially, emotionally, psychologically and physically. Gender based violence is caused by various factors such as substance abuse, lack of education as well as gender norms, socialization and aggressive behavior of men. This study explored the experiences of young women regarding gender-based violence and factors that contribute to this scourge. The research was qualitative in nature and used non-probability sampling as well as snowball and purposive sampling to gather the data. The population was young women between the ages of 12-25 from Vhufuli village. Data was collected using semi-structured interviews. The key finding of the study is that young women are experiencing sexual abuse, physical abuse, emotional abuse, economic and psychological abuse at the hands of their partners and parents. The recommendations are that policy makers need to regulate laws that will also be enforced, as a way of fighting against gender-based violence. There is a need to educate our communities about the dangers posed by patriarchy, and to also understand how hegemonic masculinities can be toxic in our communities. Social workers could also help by coming up with early intervention strategies that may assist in curbing the pandemic of domestic violence.